Predominant overexpression of CD25/FOXP3, IFN-γ, and suppressive cytokines in high-grade lesion samples infected with human papillomavirus - Camila M. Bonin; Cacilda T. J. Padovani; Alda Maria T. Ferreira; Leandro S. Ávila; Ana Paula Machado; Thiago T. M. Prata; Carlos Eurico S. Fernandes; Inês Aparecida Tozetti
ABSTRACT Introduction: Human papillomavirus (HPV) persistent infection is the leading cause of cervical cancer and its precursor lesions, and the inappropriate immune response is among the factors that contribute to viral persistence. This may be influenced by regulatory T (Treg) cells and the production of immunosuppressive cytokines, such as transforming growth factor beta (TGF-β) and interleukin-10 (IL-10). Objective: We established the profile of the predominant response, Th1 or immunosuppressive response, in the tissue microenvironment, by detecting interferon-gamma (IFN-γ), TGF-β, and IL-10, as well as the co-expression of IL-2 receptor alpha (CD25) and forkhead box P3 (FOXP3). Methods: Seventy-four samples from uterine cervix biopsies that underwent HPV deoxyribonucleic acid (DNA) detection and histopathology analysis were immunostained to detect CD25/FOXP3, IFN-γ and suppressive cytokines in lymphocytes. Results: The microenvironment of high-grade squamous intraepithelial lesion (HSIL) samples with high numbers of viral particles (≥ 10,000 copies/ml) contained high numbers of CD25/FOXP3+, TGF-β+, IL-10+, and IFN-γ+ cells. Conclusion: The co-expression of CD25/FOXP3 and the expression of TGF-β, and IL-10 in HSIL samples suggest the existence of Treg cells in these locations, although IFN-γ expression was observed in several cells in these samples. Our data suggest that this cytokine could be related to immunosuppressed microenvironment maintenance, favoring the persistent HPV infection and the progression to carcinoma.